Aktivitas Perilaku Makan Kukang Sumatera (Nycicebus coucang coucang) pada Malam Hari di Penangkaran - Semiadi, Gono; Tjakradidjaja, Anita S.; Diapari, Didid (Perhimpunan Biologi Indonesia, 2002)
ABSTRACTFeeding Behaviour Activity of Slow Loris (Nycicebus coucang coucang) at Night inCaptivity. Slow loris (Nycticebus coucang) is an endangered tropical primate, with itsdistribution in Indonesia stretch from Java, Sumatra to Kalimantan islands. Population declineare mainly due to habitat destruction, competition in feed and space and live capture to be soldas pet animals. One of the strategies to conserve the species is through captive breedingprogram (ex situ). Understanding the behaviour of slow loris in captivity, especially theirfeeding behaviour, will provide valuable information for obtaining maximal management. Thestudy was conducted at Mammals Captive Breeding, Pusat Penelitian Biologi-LIP1 in Bogor,for three months. Three adults slow loris consisting of two males and one female, were placedin individual cages and observed their nighttime feeding behaviour. Feeds that were givenconsisted of banana, marquise, guava, coconut, papaya, sweet corn, bread and quail eggs. Onezero sampling method was used in the observation with fifteen minutes interval. The resultsshowed that night feeding activity took place 12.44% of the total activities, with the highestactivity took place between 18.00-19.00 WIB as much as 6,1%. Drinking activity took placeonly 0,21% of the total activities, with defecation and urination activities were noted only3,84% and 2,73%, respectively. Others activities, such as locomotion, grooming and restingwere 14,59%, 58,08% and 8,12%, respectively, of the total activities.Keywords : Slow loris, Nycticebus coucang, captive breeding, behaviour, activities